Secondary battery and electric equipment
By using styrene-acrylate-acrylic acid copolymer in the negative electrode sheet of the secondary battery, the content in its coating is controlled, and the problem of electrolyte consumption during the circulation of the silicon-based negative electrode is solved, thereby achieving higher circulation performance and energy density.
Patent Information
- Application Number
- CN202411990424.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The volume of the silicon-based negative electrode expands during the charge and discharge cycle, resulting in a large amount of electrolyte consumption, a decrease in lithium-ion electron conduction medium, and an increase in impedance, which affects the cycle life of the secondary battery.
The styrene-acrylate-acrylic acid copolymer is introduced into the negative electrode sheet. By controlling the copolymer content in the first coating and the second coating, the absorption and release of the electrolyte are achieved, ensuring that there is enough electrolyte on the electrode surface to support ion conduction.
It effectively improves the circulation performance and energy density of the secondary battery, extends the service life of the battery, and maintains the dynamic performance.
Smart Images

Figure CN119786770A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] With the rapid popularization and promotion of electric vehicles, the demand for secondary batteries with high energy density and long cycle performance is increasing. In secondary batteries, the performance of positive and negative electrodes is one of the key factors affecting electrochemical performance. Therefore, developing negative electrodes with better performance, such as silicon-based negative electrodes, is one of the effective ways to further improve the performance of secondary batteries.
[0003] However, during the charge and discharge cycle, the silicon-based negative electrode has a high volume expansion rate, and a large amount of electrolyte will be consumed during the charge and discharge process, which will reduce the lithium ion electron conduction medium and increase the impedance, making it difficult to guarantee the cycle life of the secondary battery.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] The first purpose of the present application is to provide a secondary battery that effectively improves the cycle performance and energy density of the battery while ensuring the dynamic performance.
[0006] The second objective of the present application is to provide an electrical device.
[0007] In order to achieve the above-mentioned purpose of this application, the following technical solutions are adopted:
[0008] The present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises a first coating layer and a second coating layer, wherein the first coating layer is arranged between the second coating layer and the current collector;
[0009] The first coating layer and the second coating layer both contain styrene-acrylate-acrylic acid copolymer, and the content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is greater than the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer.
[0010] Furthermore, the content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is 1.2 wt % to 1.8 wt %.
[0011] Furthermore, the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer is 0.2 wt % to 0.8 wt %.
[0012] Furthermore, in the styrene-acrylate-acrylic acid copolymer, the weight proportion of the acrylate structural unit is 45% to 55%, and the weight proportion of the acrylic acid structural unit is 10 to 25%.
[0013] Furthermore, the negative electrode active layer contains a negative electrode active material, the negative electrode active material includes a silicon-based material and graphite, and the weight ratio of the silicon-based material to the graphite is (5-25): (75-95).
[0014] Furthermore, the styrene-acrylate-acrylic acid copolymer contains an alkali metal element, and the alkali metal element includes at least one of Na, K, and Li.
[0015] Furthermore, the mass percentage of alkali metal elements in the styrene-acrylate-acrylic acid copolymer is 0.91% to 1.52%.
[0016] Furthermore, the styrene-acrylate-acrylic acid copolymer contains carbon and oxygen, the mass percentage of the carbon is 68.5% to 72%, and the mass percentage of the oxygen is 18.3% to 22.8%.
[0017] Furthermore, the first coating layer and the second coating layer each independently contain a silicon-based material, and the content of the silicon-based material in the second coating layer is greater than the content of the silicon-based material in the first coating layer.
[0018] The present application also provides an electrical device, comprising the secondary battery as described above.
[0019] Compared with the prior art, the beneficial effects of this application are:
[0020] The secondary battery of the present application adds styrene-acrylate-acrylic acid copolymer to the negative electrode plate, and controls the content of styrene-acrylate-acrylic acid copolymer in the second coating of the negative electrode plate to be greater than the content of styrene-acrylate-acrylic acid copolymer in the first coating. The styrene-acrylate-acrylic acid copolymer absorbs part of the electrolyte by swelling itself in the initial stage. When the electrolyte concentration in the system is low in the later stage of the cycle, the styrene-acrylate-acrylic acid copolymer releases the absorbed electrolyte driven by the concentration difference, thereby ensuring that there is sufficient electrolyte on the electrode surface for ions to freely travel back and forth between the positive and negative electrodes to achieve deintercalation, thereby effectively improving the battery's cycle performance and energy density while ensuring the kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 is a Fourier infrared absorption spectrum of the styrene-methyl acrylate-acrylic acid copolymer prepared in Example 1;
[0023] Figure 2 This is the swelling diagram of the styrene-acrylate-acrylic acid copolymer of the present application;
[0024] Figure 3 This is the release of styrene-acrylate-acrylic acid copolymer on the dry electrode of this application. DETAILED DESCRIPTION
[0025] The technical scheme of the present application will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of the present application embodiments, rather than all embodiments, and are only used to illustrate the present application, and should not be considered as limiting the scope of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present application. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for the reagents or instruments used are all conventional products that can be purchased commercially.
[0026] A secondary battery and an electrical device according to an embodiment of the present application are described in detail below.
[0027] In some embodiments of the present application, a secondary battery is provided, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes a first coating layer and a second coating layer, wherein the first coating layer is disposed between the second coating layer and the current collector;
[0028] The first coating layer and the second coating layer both contain styrene-acrylate-acrylic acid copolymer, and the content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is greater than the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer.
[0029] In the negative electrode sheet of the embodiment of the present application, different contents of styrene-acrylate-acrylic acid copolymer are added to the first coating and the second coating respectively, and the content of styrene-acrylate-acrylic acid copolymer in the second coating is greater than the content of styrene-acrylate-acrylic acid copolymer in the first coating. Since the construction of solid electrolyte interface (SEI membrane) and the volume expansion of the negative electrode will lead to electrolyte loss, in addition, the electrolyte will be continuously consumed during the cycle, and the electrolyte concentration in the system will gradually decrease in the late stage of long cycle; the styrene-acrylate-acrylic acid copolymer added in the second coating is under the concentration difference, releasing the liquid absorption glue absorbed in the initial stage, ensuring that there is enough medium on the electrode surface, so that the ions can freely go back and forth between the positive and negative electrodes for deintercalation; adding a small amount of styrene-acrylate-acrylic acid copolymer in the first coating, in addition to contributing to the release of electrolyte in the late cycle, can also ensure good electronic conductivity between the negative electrode active layer and the current collector, and effectively maintain the high dynamic performance of the electrode as a whole. Specifically, in the styrene-acrylate-acrylic acid copolymer in the embodiment of the present application, the acrylate structural unit has the same -COOR structure as the ester solvent in the electrolyte and is "soluble in like". The acrylic acid structural unit exists in the form of acrylate (at least one of -COONa, -COOK, and -COOLi) structure. After the styrene-acrylate-acrylic acid copolymer contacts the electrolyte, the acrylate is ionized to form free alkali ions (Na + , K + , Li + ) and carboxylate ions, alkali ions can move freely inside the resin, and the carboxylate ions fixed on the polymer chain repel each other, causing the polymer network to expand, creating a negative pressure inside the resin, further promoting the absorption of electrolyte, thereby increasing the absorption of electrolyte.
[0030] The embodiments of the present application regulate the content of styrene-acrylate-acrylic acid copolymer in the first coating and the second coating of the negative electrode plate, thereby ensuring the conductivity of the surface of the electrode close to the current collector and the current collector, while taking into account the ability of ions to transfer between the positive and negative electrodes on the surface of the electrode close to the separator, thereby improving the kinetic performance and cycle performance.
[0031] In some embodiments, the content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is 1.2 wt % to 1.8 wt %.
[0032] In some embodiments, typically but not limiting, for example, the content of styrene-acrylate-acrylic acid copolymer in the second coating layer can be 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt% or a range of any two thereof.
[0033] In some embodiments, the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer is 0.2 wt% to 0.8 wt%; typically but not limitatively, for example, the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer can be 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt% or a range of any two thereof.
[0034] In some embodiments, the content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is M2, the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer is M1, and 0.4≤M2-M1≤1.6. The difference in the content of the styrene-acrylate-acrylic acid copolymer in the upper and lower layers is within the above range, which is conducive to further improving the cycle performance of the secondary battery.
[0035] In some embodiments, in the styrene-acrylate-acrylic acid copolymer, the weight proportion of the acrylate structural unit is 45% to 55%, and the weight proportion of the acrylic acid structural unit is 10 to 25%. In the styrene-acrylate-acrylic acid copolymer, the content of the ester group, carboxyl group and oxygen element has an effect on the liquid absorption performance and swelling performance. The weight proportion of the acrylate structural unit is 45% to 55% and the weight proportion of the acrylic acid structural unit is 10 to 25%. When added to the negative electrode plate, the negative electrode plate shows relatively good liquid absorption performance, thereby improving the cycle performance of the secondary battery.
[0036] In some embodiments, the negative electrode active layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-based material and graphite, and the weight ratio of the silicon-based material to the graphite is (5-25): (75-95). Typically but not limiting, for example, the weight ratio of the silicon-based material to the graphite in the negative electrode active material is 5:95, 10:90, 15:85, 20:80, 25:75, or a range of any two thereof.
[0037] In some embodiments, the silicon-based material includes at least one of silicon, a silicon-carbon material, and silicon oxide.
[0038] In some embodiments, the styrene-acrylate-acrylic acid copolymer contains alkali metal elements, and the mass percentage of the alkali metal elements is 0.91% to 1.52%.
[0039] In some embodiments, the styrene-acrylate-acrylic acid copolymer contains carbon and oxygen, the mass percentage of the carbon is 68.5% to 72%, and the mass percentage of the oxygen is 18.3% to 22.8%.
[0040] For silicon-based negative electrodes, the addition of styrene-acrylate-acrylic acid copolymer balances the impact of the original silicon expansion, and can further increase the content of silicon-based materials in the system, thereby playing a role in improving energy density. In some embodiments, the first coating and the second coating each independently contain silicon-based materials, and the content of silicon-based materials in the second coating is greater than the content of silicon-based materials in the first coating. Thus, the energy density of the secondary battery can be further improved while taking into account better cycle performance.
[0041] In some embodiments, the styrene-acrylate-acrylic acid copolymer can be prepared in the following manner:
[0042] (1) blending acrylic acid, an alkaline neutralizing agent and a solvent to obtain a first mixed material;
[0043] (2) adding acrylate and polystyrene to the first mixed material, and then adding an initiator to allow the acrylic acid, the acrylate and the polystyrene to undergo a polymerization reaction at 60° C. to 80° C.;
[0044] (3) The reaction system of step (2) is filtered, washed, and vacuum dried to obtain a styrene-acrylate-acrylic acid copolymer.
[0045] In step (1), the alkaline neutralizer comprises at least one of potassium hydroxide, sodium hydroxide, and lithium hydroxide, and the solvent can be deionized water. Acrylic acid can be first dissolved in deionized water, and then the alkaline neutralizer is added and stirred until uniform, for example, stirring at a stirring speed of 500rpm to 1000rpm for 30 to 120min to obtain a first mixed material. In some embodiments, the alkaline neutralizer can also be a solution of the alkaline neutralizer obtained by dissolving sodium hydroxide, potassium hydroxide, etc. in deionized water, and the molar concentration of the alkaline neutralizer solution is 10 to 15 mol / L.
[0046] In step (2), the acrylate can be methyl acrylate, ethyl acrylate, butyl acrylate, etc., and the initiator can be potassium persulfate. The initiator can be first dissolved in deionized water to obtain an initiator solution, and nitrogen is introduced into the initiator solution to remove the oxygen dissolved therein before the initiator solution is added to the first mixed material. In some embodiments, the first mixed material can be heated to 60-80°C before the initiator is added. In some embodiments, the weight ratio of acrylic acid, acrylate and styrene monomer is 1:(5-15):(5-15). In step (3), the drying temperature of vacuum drying is between 50 and 80°C. The present application uses the above-mentioned styrene-acrylate-acrylic acid copolymer or the styrene-acrylate-acrylic acid copolymer prepared according to the above method, which has liquid absorption and swelling properties in the electrolyte, thereby facilitating the improvement of battery performance.
[0047] In some embodiments, the first coating layer and the second coating layer further independently contain a negative electrode active material, a binder, and a conductive agent.
[0048] In some embodiments, the binder includes, but is not limited to, polyacrylic acid and / or styrene-butadiene copolymer.
[0049] In some embodiments, the conductive agent includes, but is not limited to, at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, and graphene.
[0050] In some embodiments, the content of the negative electrode active material in the first coating layer is 90 wt % to 96 wt %; typically but not limiting, for example, the content of the negative electrode active material in the first coating layer can be 90 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, 96 wt % or a range consisting of any two thereof.
[0051] In some embodiments of the present application, the content of the negative electrode active material in the second coating layer is 90 wt % to 96 wt %; typically but not limiting, for example, the content of the negative electrode active material in the second coating layer can be 90 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, 96 wt % or a range consisting of any two of them.
[0052] In some embodiments, in the first coating, the content of the negative electrode active material is 90wt% to 96wt%, the content of the styrene-acrylate-acrylic acid copolymer is 0.2wt% to 0.8wt%, the content of the binder is 1wt% to 5wt%, and the content of the conductive agent is 2wt% to 5wt%.
[0053] In some embodiments of the present application, in the second coating, the content of the negative electrode active material is 90wt% to 96wt%, the content of the styrene-acrylate-acrylic acid copolymer is 1.2wt% to 1.8wt%, the content of the binder is 1wt% to 5wt%, and the content of the conductive agent is 2wt% to 5wt%.
[0054] In the embodiments of the present application, styrene-acrylate-acrylic acid copolymer can replace part of the binder. Styrene-acrylate-acrylic acid copolymer is a polymer and also a glue. It can provide the function of a binder, thereby reducing the amount of binder used, increasing the load of the electrode, and further increasing the energy density and the dynamic performance.
[0055] In some embodiments, the negative electrode current collector includes at least one of a copper foil, a carbon-coated copper foil, and a composite copper foil.
[0056] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active layer. In some embodiments, the positive active layer contains a positive active material, a binder and a conductive agent. In some embodiments, in the positive active layer, the content of the positive active material is 94wt% to 96wt%, the content of the binder is 2wt% to 4wt%, and the content of the conductive agent is 1wt% to 3wt%.
[0057] In some embodiments, the positive electrode active material includes but is not limited to a ternary positive electrode material and a lithium iron phosphate positive electrode material; the binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, hydroxymethyl cellulose and polyvinyl pyrrolidone; the conductive agent includes but is not limited to at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers and graphene.
[0058] In some embodiments of the present application, a method for preparing a secondary battery is also provided, comprising the following steps:
[0059] The slurry of the first coating layer and the slurry of the second coating layer are sequentially coated on the surface of the current collector, and the negative electrode sheet is obtained after drying and rolling.
[0060] In some embodiments of the present application, a method for preparing a secondary battery comprises the following steps:
[0061] After the positive electrode sheet, separator and negative electrode sheet are wound or stacked in sequence, they are packaged, injected and formed in sequence to obtain a secondary battery. The obtained secondary battery can be a wound secondary battery or a stacked secondary battery.
[0062] In some embodiments of the present application, an electrical device is also provided, comprising the secondary battery described above.
[0063] In order to better explain the technical solutions of the embodiments of the present application, further explanations are given below through a number of specific embodiments.
[0064] Examples 1 to 7 and Comparative Examples 1 to 3
[0065] The preparation methods of the secondary batteries provided in Examples 1 to 7 and Comparative Examples 1 to 3 include the following steps:
[0066] The positive electrode sheet, the separator and the negative electrode sheet are wound in sequence to obtain a bare cell; the bare cell is packaged, dehydrated, injected with electrolyte and formed in sequence to obtain a secondary battery.
[0067] The method for preparing the positive electrode sheet comprises the following steps:
[0068] The positive electrode material (NCM622), conductive agent (conductive carbon black) and binder (polyvinylidene fluoride) are mixed in a weight ratio of 8:1:1, and then evenly coated on the positive electrode collector using an extrusion coating die (DIE). After drying and rolling, the positive electrode sheet is obtained.
[0069] The method for preparing a negative electrode sheet comprises the following steps:
[0070] Dispersing each raw material in a solvent to obtain a slurry of a first coating layer;
[0071] Dispersing each raw material in a solvent to obtain a slurry of a second coating layer;
[0072] The slurry of the first coating layer and the slurry of the second coating layer are uniformly coated on the copper foil by using an extrusion double-layer coating die (DIE), and the negative electrode sheet is obtained after drying and rolling; in the negative electrode sheet, the first coating layer and the second coating layer are sequentially stacked along the thickness direction of the copper foil, wherein the coating is double-sided coating, specifically, double-layer coating on one side is first dried and then double-layer coating is applied on the other side of the copper foil and dried, so the structure of the negative electrode sheet is "second coating layer-first coating layer-copper foil-first coating layer-second coating layer".
[0073] Among them, the electrolyte composition is 12.5wt% LiPF6 and 1wt% LiFSI dissolved in an organic solvent, and the composition and mass ratio of the organic solvent is FEC:EC:PC:EMC=1:1:1:7, wherein FEC represents ethyl methyl carbonate, EC represents ethylene carbonate, PC represents propylene carbonate; EMC represents ethyl methyl carbonate.
[0074] In Examples 1 to 4 and Comparative Examples 1 to 3, the method for preparing the styrene-acrylate-acrylic acid copolymer comprises the following steps:
[0075] Weigh 4 g of acrylic acid and place it in a three-necked flask, add 50 mL of distilled water, slowly add 12 mol / L NaOH solution dropwise while stirring in an ice-water bath, add 9 g of methyl acrylate and 7 g of polystyrene in sequence after partial neutralization, add initiator potassium persulfate, react at 70±5°C for 7 h, and after the reaction is completed, vacuum dry at 50°C to constant weight, crush, and sieve to obtain product 1 of a certain particle size.
[0076] The difference between Example 5 and Example 4 is that the addition amounts of methyl acrylate and acrylic acid used in the preparation method of styrene-acrylate-acrylic acid copolymer are different, as follows:
[0077] Weigh 2g of acrylic acid and place it in a three-necked flask, add 50mL of distilled water, slowly add 12mol / L NaOH solution dropwise while stirring in an ice-water bath, add 10g of methyl acrylate and 8g of polystyrene in sequence after partial neutralization, add initiator potassium persulfate, react at 70±5℃ for 7h, after the reaction is completed, vacuum dry at 50℃ to constant weight, crush, and sieve to obtain product 2 with a certain particle size.
[0078] The difference between Example 6 and Example 4 is that the raw materials and addition amounts used in the preparation method of styrene-acrylate-acrylic acid copolymer are different, as follows:
[0079] Weigh 3 g of acrylic acid and place it in a three-necked flask, add 50 mL of distilled water, slowly add 12 mol / L NaOH solution dropwise while stirring in an ice-water bath, add 11 g of butyl acrylate and 6 g of polystyrene in sequence after partial neutralization, add initiator potassium persulfate, react at 70±5°C for 7 h, after the reaction is completed, vacuum dry at 50°C to constant weight, crush, and sieve to obtain product 3 of a certain particle size.
[0080] The difference between Example 7 and Example 4 is that the raw materials and addition amounts used in the preparation method of styrene-acrylate-acrylic acid copolymer are different, as follows:
[0081] Weigh 5 g of acrylic acid and place it in a three-necked flask, add 50 mL of distilled water, slowly add 12 mol / L NaOH solution dropwise while stirring in an ice-water bath, add 10 g of butyl acrylate and 9 g of polystyrene in sequence after partial neutralization, add initiator potassium persulfate, react at 70±5°C for 7 h, after the reaction is completed, vacuum dry at 50°C to constant weight, crush, and sieve to obtain product 4 of a certain particle size.
[0082] A small amount of the prepared products 1 to 4 were taken for corresponding characterization:
[0083] (1) Fourier transform infrared absorption spectroscopy was used to characterize product 1. The results are as follows Figure 1 shown.
[0084] according to Figure 1 The absorption peak of product 1 can be obtained as follows: 3061cm -1 、3027cm -1 It is the stretching vibration peak of unsaturated CH on the benzene ring; 2956cm -1 、2930cm -1 、2871cm -1 It is the stretching vibration peak of -CH3 and -CH2; 1727cm -1 It is the C=O stretching vibration peak in methyl acrylate and acrylic acid; 1602cm -1 、1582cm-1 、1493cm -1 、1451cm -1 is the vibration peak of the benzene ring skeleton; 1247cm -1 、1156cm -1 、959cm -1 、942cm -1 It is the stretching vibration peak of the CO group in methyl acrylate; 759cm -1 、699cm -1 It is the out-of-plane bending vibration peak of the CH of the monosubstituted benzene ring; 553cm -1 It is the out-of-plane bending vibration peak of the benzene ring. From this, it can be determined that the product is a styrene-methyl acrylate-acrylic acid copolymer.
[0085] (2) ICP elemental analysis: Table 1 is the target product synthesized by theoretical design, and Table 2 is the ICP analysis of the product synthesized according to Table 1.
[0086] Table 1
[0087] Structural unit weight Styrene Methyl acrylate Butyl acrylate acrylic acid Target 1 35% 45% / 20% Target 2 40% 50% / 10% Target 3 30% / 55% 15% Target 4 45% / 50% 25%
[0088] Table 2
[0089] element C O H Na Product 1 68.44% 22.81% 7.23% 1.52% Product 2 71.07% 20.68% 7.51% 0.74% Product 3 70.72% 19.70% 8.67% 0.91% Product 4 71.97% 18.33% 8.38% 1.32%
[0090] It can be seen from Tables 1 and 2 that the content of each element tested by ICP is consistent with the theoretical calculated value. Target 1 corresponds to product 1, target 2 corresponds to product 2, target 3 corresponds to product 3, and target 4 corresponds to product 4, which indirectly indicates that the synthesized product is consistent with the designed target.
[0091] The swelling and release of the styrene-methyl acrylate-acrylic acid copolymer prepared in Example 4 were tested. The styrene-methyl acrylate-acrylic acid copolymer was immersed in an electrolyte with a LiPF6 content of 12.5wt% and a LiFSI content of 1wt% (the solvent is FEC:EC:PC:EMC=1:1:1:7, wherein FEC represents ethyl methyl carbonate, EC represents ethylene carbonate, PC represents propylene carbonate; and EMC represents ethyl methyl carbonate) and allowed to stand for 24h. The results are shown in FIG. Figure 2 Then, the styrene-acrylate-acrylic acid copolymer soaked and absorbed with electrolyte was transferred to laboratory filter paper, and the diffusion of styrene-acrylate-acrylic acid copolymer and electrolyte in the filter paper was observed at regular intervals. Figure 3 shown.
[0092] from Figure 2 It can be seen that when the styrene-methyl acrylate-acrylic acid copolymer is immersed in the electrolyte, it absorbs the electrolyte and swells.
[0093] from Figure 3 It can be seen that when the styrene-methyl acrylate-acrylic acid copolymer that has absorbed the electrolyte is placed in the filter paper, the electrolyte is released from the styrene-methyl acrylate-acrylic acid copolymer to the filter paper over time, and the infiltration area formed by the electrolyte diffusion into the filter paper gradually increases, while the volume of the styrene-methyl acrylate-acrylic acid copolymer gradually decreases. This shows that the styrene-methyl acrylate-acrylic acid copolymer has good electrolyte absorption and swelling properties and slow electrolyte release properties.
[0094] The raw materials and contents of the first coating layer and the second coating layer of the negative electrode sheets in Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Table 3. In Table 3, the negative electrode active materials are artificial graphite and silicon; the content of artificial graphite in the negative electrode active material is 95wt%, and the content of silicon is 5wt%; the styrene-methyl acrylate-acrylic acid copolymer is the styrene-methyl acrylate-acrylic acid copolymer or the styrene-butyl acrylate-acrylic acid copolymer prepared above; the binder is polyacrylic acid; and the conductive agent is conductive carbon black.
[0095] Table 3
[0096]
[0097]
[0098] Embodiments 8 to 13
[0099] The preparation methods of the secondary batteries provided in Examples 8 to 13 refer to Example 4, the only difference being that the silicon content in the active material is different, as shown in Table 4 for details.
[0100] Table 4
[0101]
[0102] Performance Testing
[0103] The secondary batteries prepared in Examples 1 to 13 and Comparative Examples 1 to 3 were subjected to a 50% SOC 4×40 mA constant voltage charging 10 s DCR test and a charge-discharge cycle test. The results are shown in Table 5.
[0104] The normal temperature DCR test conditions are: 50% SOC 4×40mA constant current discharge for 10s at 25℃.
[0105] The low temperature DCR test conditions are: 50% SOC 0.36×40mA constant current discharge for 10s at -20℃.
[0106] Capacity test: 1. Stand for 10 minutes; 2. 1C constant current discharge to 2.5V; 3. Stand for 10 minutes; 4. 1C constant current charge to 4.4V, then constant voltage charge to 0.05C current; 5. Stand for 10 minutes; 6. 1C constant current discharge to 2.5V; 7. Stand for 10 minutes;
[0107] Interval voltage calibration; 8. 0.33×40mA constant current charge to 4.4V and then constant voltage charge to 0.05×40mA current; 9. Stand for 15min; 10. 1×40mA constant current discharge 3456s (V0); 11. Stand for 5s, 12. 1×40mA constant current charge 216s (V1); 13. Stand for 5s; 14. 4.2×40mA constant current charge 60s (V2); 15. Stand for 5s; 16. 4.08×40mA constant current charge 159s (V3); 17. Stand for 5s; 18. 3.4 9×40mA constant current charging for 258s (V4); 19. Stand for 5s; 20. 2.98×40mA constant current charging for 121s (V5); 21. Stand for 5s; 22. 2.94×40mA constant current charging for 122s (V6); 23. Stand for 5s; 24. 1×40mA constant current charging for 360s (V7); 25. Stand for 5s; 26. 0.5×40mA constant current charging for 504s (V8); 27. Stand for 15min; 28. 1×40mA constant current discharge 2.5V; 29. Stand for 10min.
[0108] 25℃ cycle test: 1. Stand for 10min; 2. 1×40mA constant current charge to V1; 3. Stand for 5s; 4.2×40mA constant current charge to V2; 5. Stand for 5s; 6. 4.08×40mA constant current charge to V3; 7. Stand for 5s; 8. 3.49×40mA constant current charge to V4; 9. Stand for 5s; 10. 2.98×40mA constant current charge to 1. Stand for 5s; 12. Charge to V6 with 2.94×40mA constant current; 13. Stand for 5s; 14. Charge to V7 with 1×40mA constant current; 15. Stand for 5s; 16. Charge to V8 with 0.5×40mA constant current; 17. Stand for 10min; 18. Discharge to V0 with 1×40mA constant current; 19. Stand for 20min; 20. Cycle steps 2 to 19 3000 times or the capacity is as low as 80% of the nominal capacity.
[0109] 45℃ cycle test: 1. Stand for 10min; 2. 1×40mA constant current charge to V1; 3. Stand for 5s; 4.2×40mA constant current charge to V2; 5. Stand for 5s; 6. 4.08×40mA constant current charge to V3; 7. Stand for 5s; 8. 3.49×40mA constant current charge to V4; 9. Stand for 5s; 10. 2.98×40mA constant current charge to 1. Stand for 5s; 12. Charge to V6 with 2.94×40mA constant current; 13. Stand for 5s; 14. Charge to V7 with 1×40mA constant current; 15. Stand for 5s; 16. Charge to V8 with 0.5×40mA constant current; 17. Stand for 10min; 18. Discharge to V0 with 1×40mA constant current; 19. Stand for 20min; 20. Cycle steps 2 to 19 3000 times or the capacity is as low as 80% of the nominal capacity.
[0110] Table 5
[0111]
[0112]
[0113] From the comparison of Examples 1 to 4, it can be seen that when the ratio of styrene-acrylate-acrylic acid copolymer in the first coating and the second coating in the negative electrode plate changes, the performance also shows a certain change pattern. The overall kinetic performance is basically the same, but with the increase of styrene-acrylate-acrylic acid copolymer in the second coating, the cycle performance is significantly improved.
[0114] In Examples 4 to 7, as the ester and carboxyl contents decrease, the oxygen content decreases, the liquid absorption capacity of the electrode decreases, and the cycle performance decreases. At the same time, due to the change in the sodium content, the ionic conductivity fluctuates to a certain extent. The Na ion content is high and the ionic conductivity is good, and the DCR is reduced to a certain extent.
[0115] From the comparison between Examples 8 to 13 and Example 4, it can be seen that when the silicon content in the negative electrode active material gradually increases, the DCR and cycle performance can remain basically unchanged. The addition of styrene-acrylate-acrylic acid copolymer can effectively increase the amount of silicon material added. Since the silicon material has a high specific capacity, it is beneficial to further improve the overall energy density.
[0116] Those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises a first coating layer and a second coating layer, wherein the first coating layer is disposed between the second coating layer and the current collector; The first coating layer and the second coating layer both contain styrene-acrylate-acrylic acid copolymer, and the content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is greater than the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer.
2. The secondary battery according to claim 1, characterized in that: The content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is 1.2 wt % to 1.8 wt %.
3. The secondary battery according to claim 1, characterized in that: The content of the styrene-acrylate-acrylic acid copolymer in the first coating layer is 0.2 wt % to 0.8 wt %.
4. The secondary battery according to claim 1, characterized in that: The content of the styrene-acrylate-acrylic acid copolymer in the second coating layer is M2, the content of the styrene-acrylate-acrylic acid copolymer in the first coating layer is M1, and 0.4≤M2-M1≤1.
6.
5. The secondary battery according to claim 1, characterized in that: In the styrene-acrylate-acrylic acid copolymer, the weight proportion of the acrylate structural unit is 45% to 55%, and the weight proportion of the acrylic acid structural unit is 10 to 25%.
6. The secondary battery according to claim 1, characterized in that: The negative electrode active layer comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-based material and graphite, and the weight ratio of the silicon-based material to the graphite is (5-25):(75-95).
7. The secondary battery according to claim 1, characterized in that: The styrene-acrylate-acrylic acid copolymer contains alkali metal elements, and the mass percentage of the alkali metal elements is 0.91% to 1.52%.
8. The secondary battery according to claim 7, characterized in that: The styrene-acrylate-acrylic acid copolymer contains carbon and oxygen. The mass percentage of the carbon is 68.5% to 72%, and the mass percentage of the oxygen is 18.3% to 22.8%.
9. The secondary battery according to claim 1, characterized in that: The first coating layer and the second coating layer each independently contain a silicon-based material, and the content of the silicon-based material in the second coating layer is greater than the content of the silicon-based material in the first coating layer.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Battery electrode pole piece and preparation method thereof, battery and terminal
CN113690447A
Electrode plate and preparation method thereof, battery and power utilization device
CN115820047A
Secondary battery and electronic device
CN116565181A
Battery cell
CN118553909A
Negative pole piece, electrochemical device and electronic equipment
CN119069655A